Frontiers in Hydropedology: Interdisciplinary Research from Soil Architecture to the Critical Zone. Issue 1 (12th April 2018) - Li, Xiao-Yan; Lin, Henry; Gerke, Horst H.
Abstract : Core Ideas: This special section focuses on interactions between soils and hydrologic processes in landscapes. These contributions stem from the 3rd International Conference on Hydropedology. The 10 articles fall into four themes. This preface for the special section provides a brief background on hydropedology as an emerging interdisciplinary science. The 10 articles included in this special section stem from presentations given at the third International Conference on Hydropedology held in August 2016 in Beijing, China, which highlighted the importance of soil architecture and preferential flow, soil moisture and hillslope hydrology, hydrologic flux and soil structure interactions at different scales, soil biophysical and biochemical complexity, and Critical Zone science.